Optical properties of grooved silicon structures: theory and experiment - PEROVA, TANIA (My University, 2011)
The reflection spectra of grooved silicon structures consisting of alternating silicon walls and grooves (air channels) with a period of a = 4?6 ?m are studied experimentally and theoretically in the mid-IR spectral range (2?25 ?m) upon irradiation of samples by normally incident light polarized along and perpendicular to silicon layers. The calculation is performed by the scattering matrix method taking into account Rayleigh scattering losses in a grooved layer by adding imaginary parts to the refractive indices of silicon and air in grooved regions. The experimental and calculated reflection spectra are in good agreement in the entire spectral range studied. The analysis of experimental and calculated spectra gave close values of the effective refractive indices and birefringence of the studied structures in the long-wavelength spectral region. The values calculated in the effective medium model in the long-wavelength approximation (? ? a) gave considerably understated values. The obtained results confirm the efficiency of the scattering matrix method for describing the optical properties of silicon microstructures.
PUBLISHED
Keywords: Optics; grooved silicon structures; Nanoscience & Materials